Epothilone B from Aspergillus fumigatus with a strong antiproliferative and anti-tubulin polymerizing activities; apoptosis, and cell cycle analyses - Ashraf S. A. El-Sayed; Safa W. Aziz; Ahmed H. Moustafa; Noha M. Saad; Mohamed Ali (BMC Microbiology, 2025)
Abstract Epothilones were designated as one of the most recognized chemotherapeutic agents towards the drug-resistant tumors, for their higher potency to bind and stabilize the β-tubulin arrays, stopping the cell cycle. Epothilones were chemically resolved from Aspergillus fumigatus # MN744705.1, that being more affordable source than Sorangium cellulosum, for its rapid growth and unique biological behaviour. So, the aim of this work was to emphasize the chemical identity and efficacy of Aspergillus fumigatus Epothilone. The Epothilone structure of A. fumigatus was determined by HPLC, FT-IR, LC–MS analyses, with 507.7 m/z, compared to the authentic one of S. cellulosum. Aspergillus fumigatus epothilone B had the highest activity against HepG-2 (IC50 value 6.3 μM), and HCT-116 and Pc3 (IC50 value 7.4 μM), compared to Vero cells (18.7 μM) with selectivity index 2.9, 2.5, and 2.47, respectively. The anti-tubulin polymerizing potency of the purified Epothilone was about two folds more than Taxol, with an obvious resilient arrest to the cellular growth of the cells of HepG-2 at G2/M phase. The total, early and late apoptosis of the HepG2 cells were increased by 26.5%, 15.9% and 7.6%, respectively, with the epothilone of A. fumigatus, with an overall increase of apoptosis by 12 folds, compared to control. The caspase-9 and 3 activities were increased by 4 folds and 2.5 folds, with the Epothilone B, as revealed from the colorimetric activity and gene expression analyses. The level of released LDH of HepG-2 cells was increased exponentially with the Epothilone concentration, ensuring their negative effect on the plasma membrane permeability. From the docking results, the binding energy of Epothilone B with the tubulin-β was -9.96 kcal/mol, that was lower than Taxol (-7.87 kcal/mol), ensuring the higher affinity of Epothilone B to bind with the β-tubulin protein.